Introduction to the analysis of public policies - Prof. univ. dr. habil. Mihaela Rus; Lect. univ. dr. Mihaela Sandu; Tasente, Tanase (Technium Social Sciences Journal, 2020)
We can talk about public policies when a public authority - central or local - intends, with the help of a coordinated action program, to modify the economic, social, cultural environment of social actors. At national level, public policies can appear from any of the major state institutions (Parliament, President, Government, central or local authorities). The study of public policies is different from the traditional academic research, having an applied approach, oriented towards: (1) designing and developing solutions for the problems of society, (2) Interdisciplinarity, (3) Orientation towards problem solving: it does not have a purely academic character, but it is oriented towards the problems of the real world, looking for solutions for them, (4) Normativity. The general stages of this process are as follows: (1) defining the problem, (2) making the decision, (3) implementation of public policy, (4) monitoring and evaluation of public policy.